PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PEGAWAI PT. PLN NUSA DAYA SUMBAWA - Arum, Febriyanti; Muttaqillah Muttaqillah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of job satisfaction, organizational commitment, and organizational culture on Organizational Citizenship Behavior (OCB) among employees of PT. PLN Nusa Daya Sumbawa. The research employed a quantitative approach using a simple random sampling technique, involving 54 respondents from a total population of 115 employees. Data were collected through questionnaires, interviews, and documentation, and analyzed using multiple linear regression with the assistance of SPSS.The results indicate that job satisfaction has a positive and significant effect on OCB (β = 0.301; t = 2.863; p < 0.05). Organizational commitment also has a positive and significant effect (β = 0.290; t = 2.266; p < 0.05). Organizational culture has a positive and significant effect on OCB (β = 1.371; t = 11.971; p < 0.05). Simultaneously, all variables have a significant effect on OCB (F = 95.389; p < 0.05). The coefficient of determination (R² = 0.851) indicates that 85.1% of the variation in OCB is explained by these variables, while the remaining 14.9% is influenced by other factors. These findings confirm that organizational culture is the most dominant factor, followed by job satisfaction and organizational commitment. Therefore, strengthening organizational culture as well as improving job satisfaction and employee commitment are important strategies to promote extra-role behavior and enhance organizational effectiveness.